Proceedings of the 4th International Conference on Sustainable Innovation 2020-Accounting and Management (ICoSIAMS 2020) 2021
DOI: 10.2991/aer.k.210121.021
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy, Firms’ Characteristics and the Impact on the Southeast Asian Firms’ Value

Abstract: This research aims to analyze the factors determining the dividend policy of the Southeast Asian non-financial corporate sectors. In this research, the dividend policy of firms in Southeast Asia follows more closely the predictions of Modigliani-Miller theory, that dividend policy does not give impact to the firms' value, but the firms' characteristics include investment decision that supports to the firms' value. This research is verification research that aims to explain the causal relationship between the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Based on signalling theory, we could hypothesise that dividend policy mediates the effects of some variables that impact firm value, but we need empirical testing before drawing conclusions. Empirical studies conducted in some regions and sectors have found support for the mediating effect of dividend policy (Hunjra, 2018;Santoso et al, 2020;Setyabudi, 2021;Surwanti & Pamungkas, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Based on signalling theory, we could hypothesise that dividend policy mediates the effects of some variables that impact firm value, but we need empirical testing before drawing conclusions. Empirical studies conducted in some regions and sectors have found support for the mediating effect of dividend policy (Hunjra, 2018;Santoso et al, 2020;Setyabudi, 2021;Surwanti & Pamungkas, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these earnings become a source of internal funding when the company decides to reinvest the retained earnings. The company will be less dependent on external sources of funds, strengthening the owner's equity position (Surwanti & Pamungkas, 2021). Investors exhibit positive sentiments when companies pay regular and high dividends (Surwanti & Pamungkas, 2021), attracting potential investors and enhancing the firm's value, ultimately maximising the shareholder wealth.…”
Section: Introductionmentioning
confidence: 99%
“…The company will be less dependent on external sources of funds, strengthening the owner's equity position (Surwanti & Pamungkas, 2021). Investors exhibit positive sentiments when companies pay regular and high dividends (Surwanti & Pamungkas, 2021), attracting potential investors and enhancing the firm's value, ultimately maximising the shareholder wealth. The dividend decision is one of the most critical elements emphasised by companies as theories frequently link this factor with market value (Thirumagal & Vasantha, 2018).…”
Section: Introductionmentioning
confidence: 99%